Limited doses of immunotherapy use in advanced non-small cell lung cancer elderly patients with ECOG of 2 and high PDL-1 expression - Wong, Pui Yee; How, Soon Hin; Hassan, Radhiana; Abdul Azih, Muhammad Naimmuddin (Beijing Hospital and John Wiley & Sons Australia, Ltd., 2021)
The treatment landscape of lung cancer has evolved over the years; the standard of care has shifted from chemotherapy to the use of targeted therapy or immunotherapy (IO) as first-line treatment in patients with advanced non-small cell lung cancer (NSCLC). Breakthroughs were seen in 2015 and 2016 when IO demonstrated significant survival benefit compared with platinum-based chemotherapy in previously treated advanced NSCLC. The use of IO as first-line monotherapy in patients with positive PD-L1 expression was subsequently approved by the US Food and Drug Administration.1-3 In randomized clinical trials, treatment with pembrolizumab resulted in significant improvements in progression-free survival (PFS) and overall survival (OS) compared with chemotherapy alone. An updated analysis of the KEYNOTE-024 study comparing the outcomes of pembrolizumab versus platinum-based chemotherapy in treatment-naïve patients with PD-L1-positive advanced NSCLC (TPS of ≥50%) showed that the median OS was doubled following pembrolizumab treatment compared with chemotherapy (30.0 months vs 14.2 months, respectively). Fifty-four percent of those randomly assigned to chemotherapy crossed over to the pembrolizumab arm and despite that, the improvement in OS from the first analysis was maintained.2 In the KEYNOTE-042 phase III study in NSCLC patients with positive PD-L1 expression, those assigned to pembrolizumab as first-line treatment had better OS compared with those on chemotherapy.4 The IMpower 110 trial in treatment-naïve metastatic NSCLC patients with positive PD-L1 expression showed that treatment with atezolizumab resulted in significantly longer median OS and PFS compared with chemotherapy. Despite their significant benefits, IO drugs are nonetheless, expensive and not funded by the national health in most developing countries. Here, we report on three cases of advanced NSCLC with high PD-L1 expression in the absence of EGFR and ALK alterations. We report three patients who were treated with limited doses of IO showed durable partial response for more than 19 months after treatment cessation.